Etiological and Clinical Spectrum of Pancytopenia Based on Bone Marrow Examination (Journal of Medicine, 2019)
Background: Bone marrow aspiration is assessed for cytology and trephine biopsy provides overall cellularity, detection of focal lesion and infiltration. Bone marrow study plays a crucial role in identifying cause of aplastic anaemia in clinical practice. This study was carried out to see the etiological and clinical spectrum of pancytopenia based on bone marrow examination.Materials and Methods: This descriptive study was conducted in the Department of Medicine, Dhaka medical college Hospital, Dhaka, Bangladesh over a 2-year period (August 2016 to July 2018). A total 80 cases of pancytopenia were included in the study. Patients were diagnosed by hemoglobin less than 10 gm/ dL, total leukocyte count less than 4000/Cumm and platelet count less than 150000/cumm.Results: Maximum number of cases were seen in age group of 16-30 years (31.25%) and male to female ratio is 1.1:1. The commonest presenting complaint was fever in 40% (32/80) of the cases. Pallor was present in all the patients, Splenomegaly was seen in 20% (16/80) and hepatomegaly in 12.5% of the cases (10/80). Petechial hemorrhages were present in 5% (4/80). The commonest cause of pancytopenia was megaloblastic anemia (35%) and followed by aplastic anemia (32.5%).Conclusion: Pancytopenia is a common clinical problem encountered in clinical practice and the major differential diagnostic considerations of pancytopenia are aplastic anemia, megaloblastic anemia and hematological malignancies.J MEDICINE JUL 2019; 20 (2) : 68-71